2007
DOI: 10.1897/07-113r.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dilution on the exposure in sediment toxicity tests—buffering of freely dissolved concentrations and changes in mixture composition

Abstract: Some sediment toxicity tests, such as the Microtox test, are conducted by diluting either contaminated sediment or an aqueous phase with clean water. The present study aims to clarify how the dilution procedure affects the exposure of organisms. It is shown that freely dissolved concentrations of hydrophobic compounds are buffered by desorption from the sediment matrix when sediment is diluted with water. The buffering depends on the properties of the sediment matrix and contaminant. Consequently, the composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…The concentration of the leached styrene showed no relation to the total surface area of the PS beads present in the suspension, which spanned a range of 143–14,300 cm 2 for 25 mg/mL, regarding 10.0–0.1 μm beads, but had comparable C free of styrene. Chemical activities and freely dissolved concentrations of styrene in dilutions of the PS bead suspensions will be lower than those in the concentrated bead suspension, while being higher than calculated via dilution factors due to the repartitioning of styrene from the PS beads …”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…The concentration of the leached styrene showed no relation to the total surface area of the PS beads present in the suspension, which spanned a range of 143–14,300 cm 2 for 25 mg/mL, regarding 10.0–0.1 μm beads, but had comparable C free of styrene. Chemical activities and freely dissolved concentrations of styrene in dilutions of the PS bead suspensions will be lower than those in the concentrated bead suspension, while being higher than calculated via dilution factors due to the repartitioning of styrene from the PS beads …”
Section: Resultsmentioning
confidence: 85%
“…Chemical activities and freely dissolved concentrations of styrene in dilutions of the PS bead suspensions will be lower than those in the concentrated bead suspension, while being higher than calculated via dilution factors due to the repartitioning of styrene from the PS beads. 56 In the styrene toxicity test, a 50% inhibition of C. elegans' reproduction was obtained at a chemical activity of 0.080 (Supporting Information S5, Figure S14) corresponding to 24 mg styrene/L (Table 1), which exceeds freely dissolved concentrations of styrene in the concentrated PS suspensions by 1−2 orders of magnitude. We can thus exclude that the leached styrene caused the observed toxicity in the diluted PS suspensions.…”
Section: Resultsmentioning
confidence: 99%
“…1 In previous studies, C free showed less spatial heterogeneity and temporal variability than total concentrations (Artola-Garicano et al, 2003;Ter Laak et al, 2007), and were much less matrix-dependent. Measuring C free thus reduces the potential problems arising from interpretation of highly variable total concentration data based on grab sampling.…”
Section: Thermodynamic Levels and Activity Ratios Of Pahsmentioning
confidence: 90%
“…In our study, the six weeks prior sampling were relatively dry without extreme rainfall events (DMI, 2017), and exceptional variation in concentration levels in influent over time is thus not expected in the studied WWTPs. C free of HOCs in suspensions compared to total concentrations are much less affected by dilution when the matrix buffers C free (Ter Laak et al, 2007;Reichenberg and Mayer, 2006), based on observations by Artola-Garicano and coworkers (2003) on polycyclic musks in WWTP sludge suspensions. In addition to this, little variation was observed in PAH composition and temporal concentrations in WWTP influent in a resent Chinese study (Liu et al, 2017).…”
Section: Thermodynamic Levels and Activity Ratios Of Pahsmentioning
confidence: 97%
“…Wirkungstests, etwa Single‐Species‐Tests zur Bestimmung der (Gen‐)Toxizität von kontaminierten Sedimenten34 und chronische Wirkungstests35 ergänzen diese analytisch‐methodischen Ansätze. Dazu kommt der Einfluss von Versuchsbedingungen wie die Verdünnung kontaminierter Sedimente36 und Sedimentalterung37 auf die Toxizitätsmessungen unter Labor‐ und Freilandbedingungen. Schließlich werden Wirkungstests für die Bestimmung der Toxizität und deren Ursache in Sedimenten (Toxicity Identification Evaluation)38 weiterentwickelt.…”
Section: Sedimente Als Senkeunclassified